Science and Engineering Practices Elements on Physics Textbook: A Comparison Between Indonesia and Malaysia - Zahra, Alya Puspita; Pasaribu, Dian Rachel; Sulaeman, Nurul Fitriyah; Putra, Pramudiya Dwi Aristya (Jurnal Literasi Pendidikan Fisika (JLPF), 2025)
Many countries are revitalizing science subjects by strengthening the integration of science content with engineering, technology, and mathematics content and skills, creating STEM learning. However, the availability of textbooks capable of facilitating this integration remains limited. This study aims to analyze the Science and Engineering Practice content in high school physics textbooks used by Indonesian and Malaysian schools. This study is qualitative descriptive research with content analysis. The analysis was conducted on two samples of Indonesian and Malaysian books each. Content analysis is based on the SEPAR (Science and Engineering Practice Assessment Rubric) that divides Science and Engineering Practice into 8 elements. The analysis showed that Indonesian textbooks' Science and Engineering Practice content is still lacking compared to Malaysian books in all elements. The most common aspects found in Indonesian books are asking questions and defining problems. These results show that Malaysian high school physics textbooks represent many elements of Science and Engineering Practices, but there are still several elements that are not optimal. This research highlights the importance of improving the representation of  Science and Engineering Practice in Physics textbook.